1999
DOI: 10.1046/j.1365-2958.1999.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a germination operon on the virulence plasmid pXOl of Bacillus anthracis

Abstract: SummaryThe spores of Bacillus anthracis, the agent of anthrax disease, germinate within professional phagocytes, such as murine macrophage-like RAW264.7 cells and alveolar macrophages. We identi®ed a cluster of germination genes extending for 3608 nucleotides between the pag and atxA genes on the B. anthracis virulence plasmid pXOl. The three predicted proteins (40, 55 and 37 kDa in size) have signi®cant sequence similarities to B. subtilis, B. cereus and B. megaterium germination proteins. Northern blot analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
2
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 40 publications
3
92
2
2
Order By: Relevance
“…Recent sequencing and genetic studies have identified members of the gerA family of operons in other endospore-forming bacteria including Bacillus cereus (3), Bacillus anthracis (9), Bacillus halodurans (23), Clostridium acetobutylicum (Genome Therapeutics Corporation), Clostridium difficile (Sanger Centre), and Clostridium pasteurianum (GenBank). However, thus far no gerA homologs have been identified in other bacterial groups.…”
mentioning
confidence: 99%
“…Recent sequencing and genetic studies have identified members of the gerA family of operons in other endospore-forming bacteria including Bacillus cereus (3), Bacillus anthracis (9), Bacillus halodurans (23), Clostridium acetobutylicum (Genome Therapeutics Corporation), Clostridium difficile (Sanger Centre), and Clostridium pasteurianum (GenBank). However, thus far no gerA homologs have been identified in other bacterial groups.…”
mentioning
confidence: 99%
“…These sensors belong to the GerA family of germinant receptors, which are best characterized in Bacillus subtilis but which have also been studied in other Bacillus spp. (2,5,15,16,18,19,29,30).Six tricistronic gerA-like chromosomal loci (gerAA, gerAB, gerAC) plus the gerX locus carried on pXO1 exist in B. anthracis; these loci encode germinant recognition proteins (6,10,11,25). The gerS operon in B. anthracis mediates germination in response to aromatic ring structures and is required for germination in the presence of cultured M (11, 12).…”
mentioning
confidence: 99%
“…Six tricistronic gerA-like chromosomal loci (gerAA, gerAB, gerAC) plus the gerX locus carried on pXO1 exist in B. anthracis; these loci encode germinant recognition proteins (6,10,11,25). The gerS operon in B. anthracis mediates germination in response to aromatic ring structures and is required for germination in the presence of cultured M (11, 12).…”
mentioning
confidence: 99%
“…Previous reports had suggested that the GerX, GerH, and to a lesser extent the GerS receptors, are important for the establishment of anthrax infection and disease progression (Guidi-Rontani et al, 1999;Ireland and Hanna, 2002b;Kang et al, 2005;. However, recent data shows that as long as one of the genomically encoded receptors (GerH, GerK, GerL, or GerS) is present, B. anthracis spores remain fully virulent in an inhalational anthrax murine model (Carr et al, 2010).…”
Section: Bacillus Anthracis Ger Receptorsmentioning
confidence: 99%